Metal tools and cloth of the Ashkani period in Garmian Museum (selected example) - Mohammed, Dr. Wafaa Taher Mohammed; Mohammed, Asst.L. Wafaa Taher Mohammed; Karim, Muhammad Ali Karim (Sulaimani Journal for Humanities, 2025)
Metal ores are one of the most important raw materials used by humans to manufacture daily necessities, such as weapons, agricultural tools, household items, and jewelleries. There has long been a metallurgical interest in the Garmian region in southern Kurdistan. This paper deals withmetal objects include examples discovered in the Kifri district and its surroundings that are now preserved in the Garmian Museum and date back to the Parthian period, as well as pieces that have been lent and obtained by the museum and are probably date back to the Parthian period.
Keywords: Ashkani; metalwork; Garmian; cloth; tools